2017
DOI: 10.1007/s11356-017-9147-6
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic activities and coastal environmental quality: a regional quantitative analysis in southeast China with management implications

Abstract: Regional analysis of environmental issues has always been a hot topic in the field of sustainable development. Because the different levels of economic growth, urbanization, resource endowments, etc. in different regions generate apparently different ecological responses, a better description and comparison across different regions will provide more valuable implications for ecological improvement and policymaking. In this study, seven typical bays in southeast China that are a rapid developing area were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…P pools displayed a sharp rise in S1 compared to past 30-year (Figure 9), consequently, the P management in S1 would have a more significant risk impact on the environment in the future. A recent study reported that the increasing trend of P concentration in the river water would continue in the foreseeable future (Chen et al, 2018). Such increasing trends have also been observed in the United States (Stackpoole et al, 2019).…”
Section: Scenarios Simulations and Phosphorus Management In Pomelo Or...mentioning
confidence: 84%
“…P pools displayed a sharp rise in S1 compared to past 30-year (Figure 9), consequently, the P management in S1 would have a more significant risk impact on the environment in the future. A recent study reported that the increasing trend of P concentration in the river water would continue in the foreseeable future (Chen et al, 2018). Such increasing trends have also been observed in the United States (Stackpoole et al, 2019).…”
Section: Scenarios Simulations and Phosphorus Management In Pomelo Or...mentioning
confidence: 84%
“…A preliminary analysis was conduct, which was connected with the relationship between watershed economic level (GDP per capita and DPI per capita) and estuarine microplastics pollution of China, since some water quality indices have been frequently reported, such as nutrient (Chen et al, 2018) and dissolved oxygen (Wong and Lewis, 2013). The results of GDP per capita (r = −0.415, p = 0.487) and DPI per capita (r = −0.192, p = 0.757) offer a rough negative relationship without statistical significance.…”
Section: Relationship Between Microplastics Abundance and Human Activmentioning
confidence: 99%
“…It was also clear that ‘science-policy integration is a variable concept whose requirements may change over time in light of new knowledge and concerning the risks involved in the marine environment’. 27 Therefore, 60 research articles on maritime dispute resolution, ocean governance and marine environmental protection have been analysed in the context of ‘science-policy’ integration.…”
Section: Methodology – Within Case Qualitative Analysismentioning
confidence: 99%